Peperomia Ruiz & Pav. (Piperaceae) in the Água Fria River microbasin, Pedra Branca do Amapari, Amapá, Brazil - Facundes, Alessandra dos Santos; Rodrigues, Plúcia Franciane Ataíde; Brito, Adriano Castro de; Guimarães, Elsie Franklin; Pereira, Luciano Araujo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
This paper deals with Peperomia Ruiz & Pav. (Piperaceae) occurring in the Água Fria River watershed, Pedra Branca do Amapari, State of Amapá. The study involved the morphological analysis of the taxa collected in the region and tumbled in the Amapaense Herbarium, as well as field observations, as well as consulting the virtual portals of national herbariums. Descriptions, geographical distribution and a key to facilitate species identification are provided. Five taxa were recorded: Peperomia glabella (Sw.) A. Dietr. var. glabella; P. pellucida (L.) Kunth; P. pilicaulis C. DC.; P. rotundifolia (L.) Kunth; and P. serpens (Sw.) Loudon. P. rotundifolia is cited for the first time for the state of Amapá.
Keywords: Amazon; Taxonomy; Flora; Piperals